pH‐sustaining nanostructured hydroxyapatite/alginate composite hydrogel for gastric protection and intestinal release of Lactobacillus rhamnosus GG - Jihyun Kim; Shwe Phyu Hlaing; Juho Lee; Dongmin Kwak; Hyunwoo Kim; Aruzhan Saparbayeva; In‐Soo Yoon; Eunok Im; Yunjin Jung; Jin‐Wook Yoo (Wiley, 2023)
Abstract The gut microbiome is closely linked to gastrointestinal health and disease status. Oral administration of known probiotic strains is now considered a promising therapeutic strategy, especially for refractory diseases such as inflammatory bowel disease. In this study, we developed a nanostructured hydroxyapatite/alginate (HAp/Alg) composite hydrogel that protects its encapsulated probiotic Lactobacillus rhamnosus GG (LGG) by neutralizing hydrogen ions that penetrate the hydrogel in a stomach without inhibiting LGG release in an intestine. Surface and transection analyses of the hydrogel revealed characteristic patterns of crystallization and composite‐layer formation. TEM revealed the dispersal of the nanosized HAp crystals and encapsulated LGG in the Alg hydrogel networks. The HAp/Alg composite hydrogel maintained its internal microenvironmental pH, thereby enabling the LGG to survive for substantially longer. At intestinal pH, the encapsulated LGG was completely released upon disintegration of the composite hydrogel. In a dextran sulfate sodium‐induced colitis mouse model, we then assessed the therapeutic effect of the LGG‐encapsulating hydrogel. This achieved intestinal delivery of LGG with minimal loss of enzymatic function and viability, ameliorating colitis by reducing epithelial damage, submucosal edema, inflammatory cell infiltration, and the number of goblet cells. These findings reveal the HAp/Alg composite hydrogel as a promising intestinal‐delivery platform for live microorganisms including probiotics and live biotherapeutic products.